2016
DOI: 10.1097/ico.0000000000000685
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Mustard-Induced Corneal Injury Involves DNA Damage and Pathways Related to Inflammation, Epithelial-Stromal Separation, and Neovascularization

Abstract: Purpose To evaluate the toxic effects and associated mechanisms in corneal tissue exposed to vesicating agent, nitrogen mustard (NM), a bi-functional alkylating analog of chemical warfare agent sulfur mustard (SM). Methods Toxic effects and associated mechanisms were examined in maximal affected corneal tissue employing corneal cultures and human corneal epithelial (HCE) cells exposed to nitrogen mustard (NM). Results Analysis of ex vivo rabbit corneas showed that NM exposure increased apoptotic cell death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 42 publications
2
36
0
Order By: Relevance
“…In addition, NM exposure is also reported to cause an increase in the expression of cyclooxygenase‐2 (COX‐2, a key molecule involved in the prostaglandin synthesis and inflammatory and cytotoxic responses), matrix metalloproteinase‐9 (MMP‐9, plays a major role in the degradation of the basement membrane components), and angiogenic factors, namely VEGF (plays an important role in neovascularization (Fig. )) . Further elucidation of mechanisms and pathways in HCE cells related to these lesions in rabbit corneal tissue reveal that DNA damage is an early event, involving p53 and H2A.X phosphorylation, that leads to decreased cell viability and proliferation.…”
Section: Development Of Vesicant‐induced Ocular Injury Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, NM exposure is also reported to cause an increase in the expression of cyclooxygenase‐2 (COX‐2, a key molecule involved in the prostaglandin synthesis and inflammatory and cytotoxic responses), matrix metalloproteinase‐9 (MMP‐9, plays a major role in the degradation of the basement membrane components), and angiogenic factors, namely VEGF (plays an important role in neovascularization (Fig. )) . Further elucidation of mechanisms and pathways in HCE cells related to these lesions in rabbit corneal tissue reveal that DNA damage is an early event, involving p53 and H2A.X phosphorylation, that leads to decreased cell viability and proliferation.…”
Section: Development Of Vesicant‐induced Ocular Injury Modelsmentioning
confidence: 99%
“…The ex vivo rabbit corneal organ cultures are reported to be beneficial in primary screening and identification of therapies against vesicant‐induced ocular injuries . Furthermore, this culture system has also been useful to study corneal wound healing, and the injuries have been found to be similar to those occurring in vivo in the rabbit cornea . The rabbit corneas are obtained from Pel‐freez, a company that sells eyes of rabbits that are used for other purposes, which makes it cost effective and reduces the animal use in our studies.…”
Section: Development Of Vesicant‐induced Ocular Injury Modelsmentioning
confidence: 99%
See 3 more Smart Citations